The Semantics-Pragmatics Interface: The Case of the Singular Feminine Demonstrative in Jordanian Arabic - Samer Omar Jarbou (East European Journal of Psycholinguistics, 2017)
The aim in this study is to investigate the interface between semantics and pragmatics in relation to the use of the indexical demonstrative ‘haay’ ‘this-S.F.’ in Jordanian Arabic (JA). It is argued here that an analysis of meaning in relation to context-sensitivity inherent in the use of ‘haay’ can give evidence to the view that semantic and pragmatic processes can be distinguished from each other. I have found that the meaning of ‘haay’ consists of three distinct levels: linguistic, semantic, and pragmatic meaning. The denotational and conventional senses of ‘haay’ comprise its linguistic meaning, its semantic meaning is generated when any of the variables in the linguistic meaning is selected in relation to 'narrow context', the pragmatic meaning depends on relating the semantic meaning to an entity in the physical context of interaction. The results of this study support the view that the boundary between semantics and pragmatics can be distinctively demarcated.References Agha, A. (1996). Schema and superposition in spatial deixis. Anthropological Linguistics,38(4), 643–682. Ariel, M. (2002). The demise of a unique concept of literal meaning. Journal ofPragmatics, 34(4), 361–402.Bach, K. (1994). Conversational impliciture. Mind and Language, 9(2), 124–162.Bach, K. (1997). The semantics-pragmatics distinction: What it is and why it matters,Linguistiche Berichte, 8, 33–50.Bach, K. (2001). You don’t say? Synthese, 128(1), 15–44.Bach, K. (2012). Context dependence. In: The Continuum Companion to the Philosophy ofLanguage, (pp. 153–184). M. García-Carpintero & M. Kölbel (eds.). New York:Continuum International.Bartsch, R. (1996). The myth of literal meaning. In: Language Structure and LanguageUse: Proceedings of the International Conference on Lexicology and Lexical Semantics.Munster, 1994, (pp. 3–16). E. Weigand and F. Hundsnurscher (eds.). Tubingen: Niemeyer:.Berg, J. (2002). Is semantics still possible? Journal of Pragmatics, 34(4), 349–59.Braun, D. (2008). Complex demonstratives and their singular contents. Linguisticsand Philosophy, 31(1), 57–99.Cappelen, H. & Lepore, E. (2005). Insensitive Semantics: A Defense of SemanticMinimalism and Speech Act Pluralism. Oxford: BlackwellCarston, R. (2008). Linguistic communication and the semantics-pragmatics distinction.Synthese, 165(3), 321–345.Clark, H. (1996). Using Language. Cambridge: Cambridge University Press.Dascal, M. (1987). Defending Literal Meaning. Cognitive Science, 11(3), 259–281.Doerge, C. F. (2010). The collapse of insensitive semantics. Linguistics and Philosophy,33(2), 117–140.Gazdar, G. (1979). Pragmatics: Implicature, Presupposition, and Logical Form. NewYork: Academic Press.Gibbs, R. W. (1984). Literal meaning and psychological theory. Cognitive Science, 8(3),275–304.Gibbs, R. W. (1994). The Poetics of Mind. Cambridge: Cambridge University Press.Gibbs, R.W. (1999). Speakers’ intuitions and pragmatic theory. Cognition, 69(3), 355–359.Gibbs, R. W. & Moise, J. F. (1997). Pragmatics in understanding what is said. Cognition,62(1), 51–74.Giora, R., (1997). Understanding figurative and literal language: the graded saliencehypothesis. Cognitive Linguistics, 8(3), 183–206.Giora, R. (1999). On the priority of salient meanings: studies of literal and figurativelanguage. Journal of Pragmatics, 31(7), 919–929.Giora, R. (2002). Literal vs. figurative language: different or equal? Journal ofPragmatics, 34(4), 487–506.Grice, H.P. (1978). Further notes on logic and conversation. In: Syntax and Semantics, 9,P. Cole (ed.). (pp.113–127). New York: Academic Press; reprinted in H.P. Grice (1989).Studies in the Way of Words. Cambridge, MA: Harvard University Press.Hanks, W. (1990). Referential practice: Language and lived space among the Maya.Chicago: The University of Chicago Press.Huang, Y. (2007). Pragmatics. Oxford: Oxford University Press.Jarbou, S. O. (2012). Medial deictic demonstratives in Arabic: Fact or fallacy.Pragmatics, 22(1), 103–118.Kaplan, D. (1977). Demonstratives. In: Themes from Kaplan, J. Almog, J. Perry, andH. Wettstein (eds.). (pp. 481–563). New York: Oxford University Press.Katz, J. J. (1977). Propositional structure and Illocutionary Force. New York: ThomasY. Crowell.Kempson, R. (1988). Grammar and conversational principles. In: Linguistics,F. Newmeyer (ed.). The Cambridge Survey, Vol. II (pp. 139–163). Cambridge:Cambridge University Press.Lakoff, G. (1987). Women, Fire, and Dangerous Things: What Categories Reveal aboutthe Mind. Chicago: University of Chicago Press.Lee, C. J. (1990). Some hypotheses concerning the evolution of polysemous words.Journal of Psycholinguistic Research, 19, 211–219.Lepore, E., & Ludwig, K. (2000). The semantics and pragmatics of complexdemonstratives. Mind, 109(434), 199–240.Levinson, S.C. (1995). Three levels of Meaning. In: Grammar and meaning. Essays inHonour of Sir John Lyons, (pp. 90–115). F.R. Palmer (ed.). Cambridge: CambridgeUniversity Press.Levinson, S. C. (2006). Deixis and pragmatics. In: The Handbook of Pragmatics. (pp.97–121), L. Horn and G. Ward (eds.). Malden, MA: Blackwell Publishing.MacCormac, E. R. (1985). A Cognitive Theory of Metaphor. Cambridge, MA: MIT Press.Manning, P. (2001). On social deixis. Anthropological Linguistics, 43(1), 54–100.Nicolle, S. & Clark, B. (1999). Experimental pragmatics and what is said: a response toGibbs and Moise. Cognition, 69(3), 337–354.Recanati, F. (1989). The pragmatics of what is said. Mind and Language, 4(4), 295–329.Recanati, F. (1993). Direct Reference: From Language to Thought. Blackwell, Oxford.Recanati, F. (1995). The alleged priority of literal interpretation’. Cognitive Science, 19,207–232.Recanati, R. (2002). Unarticulated constituents. Linguistics and Philosophy, 25(3), 299–345.Recanati, F. (2004). Literal Mmeaning. Cambridge: Cambridge University Press.Rumelhart, D., E. (1979). Some problems with the notion of literal meaning. In:Metaphor and Thought. (pp. 78-90), A. Ortony (ed.). Cambridge: Cambridge UniversityPress.Searle, J. R., (1978). Literal meaning. Erkenntnis, 13(1), 207–224.Silverstein, M. (1976). Shifters, linguistic categories, and cultural description. In:Meaning in Anthropology. (pp. 11–56), K. Basso, & H.A. Selby (eds.). Albuquerque:School of American Research, University of New Mexico Press.Sperber, D. and Wilson D. (1986). Loose talk. Proceedings of the Aristotelian Society,86(1985-6), 153–171.Stalnaker, R. (1972). Pragmatics. In: Semantics for Natural Language. (pp. 380–97), D.Davidson and G. Harman (eds.). Dordrecht: Reidel.Stokke, A. (2010). Intention-sensitive semantics. Synthese 175, 383–404.Sweetser, E. (1990). From Etymology to Pragmatics. Cambridge: Cambridge UniversityPress.Vicente, B. (2002). What pragmatics can tell us about (literal) meaning: A critical note onKent Bach’s theory of impliciture. Journal of Pragmatics, 34(4), 403–421.